Recent Advances and Perspectives on the Health Benefits of Urolithin B, A Bioactive Natural Product Derived From Ellagitannins - Chen, Peng; Guo, Zhiei; Chen, Fuchao; Wu, Yue; Zhou, Benhong (Frontiers in Pharmacology, 2022)
Urolithin (Uro) B, a gut microbiota-derived metabolite from ellagitannins (ETs) and ellagic acid (EA), is a naturally occurring polyphenol abundantly found in pomegranates, raspberries, blueberries and chestnuts. Uro B has recently garnered considerable attention owing to its wide range of nutraceutical effects and relatively high potency. According to several studies, Uro B prevents the development of hyperlipidemia, cardiovascular disease (CVD) and tumors due to its strong antioxidant and anti-inflammatory properties. Many reviews have systematically summarized the health benefits and pharmacological activities of ETs, EA and urolithins (especially Uro A) while available reviews or detailed summaries on the positive impact of Uro B are rarer. Here, we sought to review the pharmacological activity, mechanism of action, regulation of immune function and its associated diseases and preventive potential of Uro B to elucidate its function as a nutritional agent in humans.